(3eHGOF GdJehjd (B/s - (3GdMGL, WGQbs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2002)
(3WHjYI GdJehjd(B- (3GdJehjd HGdEaJQGV(B- (3GdEFJeGf GdeUQaj(B- (3GdahGFO GdHSjWI(B- (3NUe GdOjhf GdbUjQI GdCLd(B- (3GdJehjd Whjd GdCLd(B- (3CehGd GdedcjI(B- (3GdJehjd GdNGQLj GdNGU(B- (3GdJehjd HGdbQhV GdYGeI(B- (3eDSSGJ GdJehjd GdOhdjIs
Keywords: (3GdEFJeGf GdeUQajs; (3GdJehjds